Implantation of medicinal housing in primary care as an instrument for health promotion: experience report (Research, Society and Development, 2020)
The use of medicinal plants has been growing steadily in Dentistry, due to its great phytotherapic importance, low cost and easy access. The report brings the experience of the implantation of a medicinal garden in the Basic Health Unit Rita Palmeira, in the city of Patos. Paraíba, Northeast Brazil, by the students of the Biological Sciences and Dentistry course at the Federal University of Campina Grande. The medicinal garden cultivates the use of medicinal species for the treatment and cure of diseases. There happened the cultivation of some plants present in the Caatinga region, such as Aloe Vera, Mint leaf and Terramicina. In addition to cultivation, lectures were given to the people present, thus disseminating knowledge among students and professionals from different health areas, in addition to the community served by that unit.